Short-term impact of acute uncomplicated malaria on the cognitive performance of school children living in an endemic area - Masyitah Masyitah; Lily Rahmawati; Sri Sofyani; Munar Lubis; Iskandar Z. Lubis (Paediatrica Indonesiana, 2009)
Background In Indonesia, malaria remains a public healthproblem. In North Sumatra between 2000 and 2004, an estimated50,670 clinical cases occurred every year, leading to the deathsof 9-10 people per year.Objectives To determine the short-term impact of acute uncompli-cated malaria on the cognitive performance of school children.Methods A prospective study was conducted on students at fourelementary schools in Madina, North Sumatra, Indonesia, fromAugust 15 to September 3, 2006. Subjects were classified intomalaria and non-malaria groups based on microscopically confirmedblood smears; they were selected by means of random sampling.Cognitive performance was measured with two examination paperson mathematics and Indonesian language before and two weeksafter artesunate and amodiaquin treatment for three days in themalaria group. Independent or paired t-tests were used to analyzedifferences in mean scores of cognitive performance.Results From 925 children examined, 384 suffered from malaria.One-hundred and thirty three children were recruited from themalaria group and 132 children were recruited from the non-malaria group. There was no difference in the distribution ofgeneral characteristics of the subjects. There was a significantdifference in cognitive performance between the malaria andnon-malaria groups (P<0.0001) before and after treatments. Inthe malaria group, there was a significant difference in cognitiveperformance before (mean 38.9; SD 15.19) and after treatment(mean 72.9; SD 10.41) with P<O.OOOl.Conclusion Acute uncomplicated malaria significantly affectsthe cognitive performance of school children living in a malaria-endemic area.